Evaluation of Ayush-64 (a Polyherbal Formulation) and Its Ingredients in the Syrian Hamster Model for SARS-CoV-2 Infection Reveals the Preventative Potential of Alstonia scholaris - Zaigham Abbas Rizvi; Upasna Madan; Manas Ranjan Tripathy; Sandeep Goswami; Shailendra Mani; Amit Awasthi; Madhu Dikshit (MDPI AG, 2023)
In the current study, we evaluated the efficacy of Ayush-64 (A64), a polyherbal formulation containing Alstonia scholaris (L.) R. Br. (A. scholaris), Caesalpinia crista L. (C. crista), Picrorhiza kurroa Royle ex Benth (P. kurroa), and Swertia chirata (Roxb.) H. Karst. (S. chirata) against COVID-19 in a Syrian hamster infection model. Preventative use of A64 resulted in the late-phase recovery of body weight loss in severe acquired respiratory syndrome coronavirus-2 (SARS-CoV-2)-infected hamsters, suppression of pro-inflammatory cytokines, and blunted pulmonary pathology. In addition, we also investigated the efficacy of individual ingredients of A64, viz., A. scholaris, C. crista, P. kurroa, and S. chirata, in the hamster model. The hamster challenge data showed robust anti-viral and immunomodulatory potential in A. scholaris, followed by P. kurroa. However, C. crista and S. chirata of A64 showed prominent immunomodulatory potential without limiting the lung viral load. In order to better understand the immunomodulatory potential of these herbal extracts, we used an in vitro assay of helper T cell differentiation and found that A. scholaris mediated a more profound suppression of Th1, Th2, and Th17 cell differentiation as compared to A64 and other ingredients. Taken together, our animal study data identifies the ameliorative potential of A64 in mitigating coronavirus disease-19 (COVID-19) pulmonary pathology. A. scholaris, a constituent extract of A64, showed relatively higher anti-viral and immunomodulatory potential against COVID-19. The present study warrants further investigations to identify the active pharmaceutical ingredients of A. scholaris for further studies.